Response to Chemotherapy in Patients with Gestational Trophoblastic Neoplasia in A Tertiary Hospital in Indonesia - Farisa Raudina; Yudi Mulyana Hidayat; Sylvia Rachmayati (Althea Medical Journal, 2020)
Background: The incidence of gestational trophoblastic neoplasia (GTN) is high in Indonesia. Based on the FIGO prognostic score, GTN is classified into low-risk and high-risk categories. The high-risk group requires multidrug chemotherapy whereas the low-risk group requires single-drug chemotherapy. Response to chemotherapy would reflect the remission rate. The aim of this study was to describe the response to chemotherapy in GTN patientsMethods: This was a cross-sectional descriptive retrospective study on medical records of patients with GTN treated in Dr. Hasan Sadikin General Hospital during the period of 2016 to 2018. The inclusion criteria were GTN patients who received > 3 cycles of chemotherapy while the exclusion criteria were incomplete, inaccessible, or missing data. Data were collected on patient’s age, parity, history of previous pregnancy, pregnancy-therapy interval, tumor size, number and location of metastases, and history of failed chemotherapy.Results: Of the189 medical records of the GTN patient collected, only 88 met the inclusion criteria, (63.6% low risk and 36.4% high risk). Most patients were responsive to chemotherapy (61.4%), aged<40 years old, multiparity, tumor size >5 cm, had 4 month interval from previous pregnancy <4 months, had a history of molar pregnancy, had no metastases, and no previous failed chemotherapy.Conclusion: The chemotherapy response in gestational trophoblastic neoplasm patients is fairly good with most patients are in the low-risk groups. Specific tumor markers used in early diagnosis of GTN may play a major role.